Climate drives among-year variation in natural selection on flowering time - Ehrlén, Johan; Valdés, Alicia (Stockholm University, 2020)
data_indiv: This data set includes 22 years of data on flowering phenology and fitness of the perennial herb Lathyrus
vernus , as well as climatic data from the same years (see below). Plant data was collected in a population of L.
vernus in a deciduous forest in the
Tullgarn area, SE Sweden (58.9496 N, 17.6097 E), during 1987–1996
and 2006–2017. In
1987, all flowering individuals in an area of 825 m²
were permanently marked and surveyed in each year to 1996. New
flowering individuals in the plot were included in the study in each
year. No recordings were made 1997–2005. In 2006, a new set of
individuals in an area of 162 m²
within the same population were marked, and surveyed in the same way
as the initially marked individuals to 2017. In total, we recorded
2411 flowering events, and followed 606 individuals 1987–1996, and
228 individuals 2006–2017.
climate_1961_2017: This data set includes climatic data from nearby stations for the period 1961-2017. Weather
data for March, April and May 1961–2017 was obtained from the
Swedish Meteorological and Hydrological Institute (www.smhi.se (http://www.smhi.se/) ). Daily mean, minimum and maximum temperature values were averaged from
two meteorological stations: Oxelösund (58.6777 N, 17.1223 E, 41 km
from the study population) and Södertälje (59.2142 N, 17.6289 E, 29
km from the study population). Daily
precipitation values were obtained from a third station located in
Åda (58.9279 N, 17.5358 E, 5 km from the study population). We calculated 12 variables from weather
data: monthly averages of daily minimum, mean and maximum
temperatures, and monthly sums of precipitation, for March, April and
May in the year of flowering.
See the article for further information.
Keywords: Ecology not elsewhere classified; Ecology; Ekologi